Evolution of Distinct Responses to Low NAD+ Stress by Rewiring the Sir2 Deacetylase Network in Yeasts. Issue 4 (1st April 2020) - Humphrey, Kristen M; Zhu, Lisha; Hickman, Meleah A; Hasan, Shirin; Maria, Haniam; Liu, Tao; Rusche, Laura N
Abstract: Evolutionary adaptation increases the fitness of a species in its environment. It can occur through rewiring of gene regulatory networks, such that an organism responds appropriately to environmental changes. We investigated whether sirtuin deacetylases, which repress transcription and require NAD + for activity, serve as transcriptional rewiring points that facilitate the evolution of potentially adaptive traits. If so, bringing genes under the control of sirtuins could enable organisms to mount appropriate responses to stresses that decrease NAD + levels. To explore how the genomic targets of sirtuins shift over evolutionary time, we compared two yeast species, Saccharomyces cerevisiae and Kluyveromyces lactis, that display differences in cellular metabolism and life cycle timing in response to nutrient availability. We identified sirtuin-regulated genes through a combination of chromatin immunoprecipitation and RNA expression. In both species, regulated genes were associated with NAD + homeostasis, mating, and sporulation, but the specific genes differed. In addition, regulated genes in K. lactis were associated with other processes, including utilization of nonglucose carbon sources, detoxification of arsenic, and production of the siderophore pulcherrimin. Consistent with the species-restricted regulation of these genes, sirtuin deletion affected relevant phenotypes in K. lactis but not S. cerevisiae . Finally, sirtuin-regulated gene sets were depleted for broadly conserved genes, consistent with sirtuins regulating processes restricted to a few species. Taken together, these results are consistent with the notion that sirtuins serve as rewiring points that allow species to evolve distinct responses to low NAD + stress.